(untitled) (Italian Journal of Public Health, 2011)
Two years ago, speaking about the future of the Italian Journal of Public Health, we told that the reason why the journal is also an international journal (almost 40% of published papers come from outside Italy) is “mainly due to our membership to EUPHA and to several scientific network”.